Structural and optical characterization of SnS thin films by electrodeposition technique - Mariappan, R.; Ragavendar, M.; Ponnuswamy, V. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
SnS thin films were electrodeposited on ITO (indium tin oxide) glass substrates maintained at different temperatures using aqueous solutions containing 33 mM of SnCl2 and 91 mM of Na2S2O3·5H2O. The films were characterized to study the structural, morphological and optical properties. The X-ray diffraction studies of the films show the polycrystalline nature with orthorhombic crystal structure. Microstructural parameters such as crystallite size, microstrain, and dislocation density were calculated with respect to various temperatures. The scanning electron microscope (SEM) studies reveal good surface morphology with a large number of grains at the optimized temperature. The optical band gap of the SnS film was determined from optical transmittance data, in the spectral range 400–1100 nm and the direct band gap energy (Eg) was found to be 1.2 eV, which does agree well with earlier reported values. Fourier transform infrared spectroscopy (FTIR) studies confirm the presence of SnS films in the molecular structure.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 989-997
Keywords: optyka; tin sulphide (SnS) thin films; cathodic electrodeposition; X-ray diffraction; SEM